Packaging Sebagai Media Komunikasi Visual Branding Kerajinan Purun Pedamaran Kepada Generasi Z Di Kota Palembang - Azizah, Niken; Windu Viatra, Aji; Patriansah, Mukhsin (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
Purun crafts have a number of unique qualities as cultural heritage with the main ingredient being purun. The purun raw material processing system is able to give a natural and ecological impression to each craft. Traditional designs with distinctive woven patterns reflect cultural identity and local values as well as natural colors without additional coloring highlighting the natural beauty of the purun plant itself, environmentally friendly manufacturing processes without negative impacts on the environment and innovation in design presenting products that remain relevant to the world. modern market. As consumer trends and preferences change, purun products may experience a lack of innovation in design or function. This branding aims to reintroduce and maintain the cultural value of Purun crafts in Palembang City, especially for those aged 17 - 26 years, so that they can restore the functional value of Purun crafts from economic, fashion and cultural aspects, as well as involving them actively through social media, and Integrating modern technology can be effective steps to introduce and popularize purun crafts among the younger generation. Keywords : Branding, Purun Crafts, Generation Z, Palembang